PENINGKATAN NILAI TAMBAH PRODUK MELALUI TEKNOLOGI TEPAT GUNA TERPADU USAHA KELOMPOK TANI PEMBUAT ARANG DI DESA AIR PUTIH KABUPATEN BENGKULU TENGAH - Andy Makhrian; Fachri Eka Saputra; Dessy Triana (Universitas Bengkulu, 2017)
Dedication this aims to provide an understanding, knowledge and life skills to the group of Harapan Maju farmers in Air Putih Bengkulu Tengah. The purpose of this program is toenhance the knowledge and skills of farmers in sewage treatment coconut shell that hasnot been utilized to the maximum so it could be a better economic value namely intocharcoal briquettes which in turn can help improve the economy of the community inHarapan Maju The farmer groups. The target audience or target group of partners in thisservice activitiy is a group of farmers in Desa Air Putih Kecamatan Talang EmpatKabupaten Bengkulu Tengah. “Harapan Maju” The farmer groups established in 2010 bycovering 20 members. The method in this devotion agribusiness approach in this studyconsider the structure and linkage of existing subsystems include technological innovations and institutional. Indicators of success seen from the role of each householdpeople started doing the processing of coconut shell charcoal and further into processingwaste into charcoal briquettes. The final target of this devotion in “Harapan Maju” Thefarmer groups in Desa Air Putih Kabupaten Bengkulu Tengah obtain increased knowledgeand skills about waste into briquettes coconut shell charcoal.Keywords: Appropriate Technology, Charcoal, Coconut Shell, Farmers